Assessment of effectiveness of delayed cord clamping and umbilical cord milking in early term and preterm infants - Jain, Mahendra K.; Bhedru, Nidhi; Jain, Anubhuti (International Journal of Contemporary Pediatrics, 2018)
Background: Early cord clamping and cutting of the umbilical cord is widely practiced as part of the management of labor; it could deprive the neonate of about a quarter of its blood volume and iron. This thesis is aimed at comparing effects of delayed cord clamping versus umbilical cord milking at birth in preterm and early term infants. Methods: This single centered randomized study was conducted in Department of Pediatrics and data collection was done on the basis of the preterm and early term infants delivered by vaginal or cesarean delivery in Department of Gynecology, Geetanjali Medical College and Hospital, Udaipur during period of January 2016 to January 2017. Total of 120 infants were included in the study. Results: Statistically it has been analyzed that in both pre-term and early term infants who underwent DDC and UCM, there was insignificant difference in level of hemoglobin (Hb), haematocrit (HCT), blood sugar, bilirubin level (TSB) and temperature of body. On the other hand, significant difference was observed in weight and cord pH of neonates of both groups. There is also insignificant difference in terms of NICU admission for RDS, sepsis, phototherapy, need of oxygen, saline boluses, PRBC transfusion, polycythemia. Conclusions: Thus, overall it was observed that there is insignificant difference in delayed cord clamping and umbilical cord milking group. Thus, both are found to be equally effective in improving hematologic parameters.